2021
DOI: 10.1007/s40744-021-00380-2
|View full text |Cite
|
Sign up to set email alerts
|

A Pooled Analysis Reporting the Efficacy and Safety of Secukinumab in Male and Female Patients with Ankylosing Spondylitis

Abstract: Introduction: Despite of higher disease burden, lower efficacy to biologics has been reported in female compared to male patients with ankylosing spondylitis (AS). The aim of this study was to evaluate the efficacy and safety of secukinumab by sex in patients with active AS from five phase 3 studies (MEASURE 1-5) through 52 weeks. Methods: Baseline demographics, disease characteristics and efficacy outcomes at Weeks 16 and 52 were summarized for males versus females. Baseline predictor analysis used multivaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
3
8
0
Order By: Relevance
“…Such an abundance of female patients ultimately allowed us to better grasp the role of gender in the response to secukinumab. Women are known to show poorer responses to TNFi compared to men in both AS and PsA, while the influence of gender in IL-17i responses appears more controversial [38]. In AS, male patients more frequently achieved inactive disease (ASDAS-ID response) in a post-hoc pooled analysis of all MEASURE trials, although no other efficacy outcomes were substantially affected by sex [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an abundance of female patients ultimately allowed us to better grasp the role of gender in the response to secukinumab. Women are known to show poorer responses to TNFi compared to men in both AS and PsA, while the influence of gender in IL-17i responses appears more controversial [38]. In AS, male patients more frequently achieved inactive disease (ASDAS-ID response) in a post-hoc pooled analysis of all MEASURE trials, although no other efficacy outcomes were substantially affected by sex [38].…”
Section: Discussionmentioning
confidence: 99%
“…Women are known to show poorer responses to TNFi compared to men in both AS and PsA, while the influence of gender in IL-17i responses appears more controversial [38]. In AS, male patients more frequently achieved inactive disease (ASDAS-ID response) in a post-hoc pooled analysis of all MEASURE trials, although no other efficacy outcomes were substantially affected by sex [38]. Furthermore, real-world evidence with secukinumab suggests that male patients show higher retention rates than females in AS and axial SpA, either statistically [31,32] or at least numerically [39].…”
Section: Discussionmentioning
confidence: 99%
“…The findings on gender were consistent with the MEASURE studies, where efficacy and safety outcomes were comparable between male and female axSpA patients treated with secukinumab over 52 weeks. 40 In the real-word German AQUILA study in r-axSpA, the secukinumab retention rate between male and female patients was not significantly different. 41 In pooled analyses of the MEASURE studies, secukinumab was effective in patients with r-axSpA regardless of their HLA-B27 status; however, patients who were HLA-B27 positive seemed to derive increased therapeutic benefit than those who were HLA-B27 negative.…”
Section: Discussionmentioning
confidence: 92%
“…Second, the study was focused on TNFi, and newer treatments were not analyzed due to sample size limitations. In this sense, a post hoc analysis of the pooled data from the MEASURE trials disclosed no sex differences on the response to secukinumab in axial SpA patients (9), while another study found worse responses among women (10). Third, this is an analysis of a database not specifically designed to look for sex or gender differences, so some variables with a potential influence on treatment response possibly were not collected.…”
Section: Discussionmentioning
confidence: 99%
“…For example, female patients have lower response rates to TNF inhibitors (TNFi) and a lower adherence to the treatment (4,7,8). Regarding IL‐17i, fewer data are available, and while sex was not an independent predictor of treatment response to secukinumab in 1 study (9), another study disclosed that male sex was associated with a lower risk of secukinumab discontinuation in patients with axial SpA and psoriatic arthritis (10). Several studies on sex differences in patients with axial SpA have revealed different biologic mechanisms that could hypothetically contribute to the observed differences in disease manifestations and treatment response (5,6).…”
Section: Introductionmentioning
confidence: 99%